Urban Entrepreneurialism and Sustainable Development: A Comparative Analysis of Chinese Eco-Developments. Issue 1 (2nd January 2020) - Xie, Linjun; Cheshmehzangi, Ali; Tan-Mullins, May; Flynn, Andrew; Heath, Tim
ABSTRACT: In recent years, state entrepreneurialism and the notion of (urban) sustainability have become ever more closely intertwined in China and there has been a proliferation of eco-/low-carbon and other similar sustainability-themed urban initiatives that have helped local states to achieve a favorable position in city competitions. Nevertheless, existing studies do not explain why Chinese sustainability projects are planned/implemented with divergent emphases and different development trajectories. Through three Chinese flagship projects, the real-estate-centric Sino-Singapore Tianjin Eco-City (SSTEC), the environmental-construction-led Chongming Eco-Islands (CEIs), and the industrial development-focused Shenzhen International Low-Carbon City (ILCC), we argue that the formulation and implementation of urban sustainable developments are subject to local particularities and different extra-local political-economic contexts. We highlight how both vertical administrative governance and horizontal coordination between territorial jurisdictions underlie the Chinese entrepreneurial planning system, which results in different types of urban entrepreneurships: (1) scalable startup urban entrepreneurship (SSTEC); (2) asset-replacement urban entrepreneurship (CEIs); and (3) urban expansion entrepreneurship (ILCC). This study also reveals that all three cases experience a development paradox as they strive to reconcile mutually competing economic and environmental imperatives.